Development of a novel scorpionate ligand with 6-methylpyridine and comparison of the structural and electronic properties of nickel(ii) complexes with related tris(azolyl)borates. Issue 27 (15th June 2022) - Fujiwara, Yusuke; Takayama, Tomoaki; Nakazawa, Jun; Okamura, Masaya; Hikichi, Shiro
Abstract : A facially-capping tris(6-methylpyridyl)phenylborate is highly electron-donating and its nickel complex is potent m CPBA activator. Abstract : A novel anionic tridentate borate ligand with a 6-methylpyridyl donor, Tpy Me, has been synthesized. Comparison of the molecular structures and reactivities of nickel(ii )-bromido complexes with tris(azolyl)borate ligands composed of pyridyl, pyrazolyl, or oxazolinyl donors indicates the characteristic sterically demanding nature and strong electron donating ability of Tpy Me .